Optical neuroimaging of executive function impairments in food addiction - Tania Alexandra Couto; Meng-Yun Wang; Zhen Yuan (Journal of Innovative Optical Health Sciences, 2022)
This study investigated the neural mechanisms located in the prefrontal cortex (PFC) involved in maintaining addictive-like eating behavior. Therefore, we aimed to fill a gap in the existing literature and help clarify the food addiction (FA) cycle by inspecting the relationship between the executive control and psychopathology involved in the FA cycle. Twenty-three students recruited from the University of Macau participated in this study. We investigated a hemodynamic response captured by NIRS recordings, activated during n-back, set-shifting, and go/no-go paradigms. Moreover, we investigated the FA symptoms through the YFAS clinical inventory to better understand the relationship between hemodynamic response and clinical symptomatology in college students. First, the hemodynamic findings confirm that altered cognitive control in executive function performance appears to be linked to addictive-like eating behaviors, which in turn confirms a circuit similarity between FA and the substance abuse population (SUD) as reported in previous fMRI studies. Secondly, the psychological findings confirm the significant association between the working memory deficits and symptoms severity which suggest the role of self-control and regulation in limiting the storage resources as a potential trigger to develop overconsumption episodes in the FA cycle. Our findings highlight how disrupted self-control and regulation of craving and negative affect induced by mental imagery might shape and overload the working memory storage as a potential trigger to develop binge eating episodes to maintain the FA cycle. In conclusion, the use of fNIRS in the context of eating disorders studies represents a valuable application, noninvasive, and patient-friendly tool, providing new insights into understanding the addiction cycle and treatment guidelines.